Fact-Checking and Check-Worthiness Determination on Tempo.co during Covid-19 Pandemic - Annisa Nurul Hanifah; Zainuddin Muda Z. Monggilo (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
Fact-checking journalism appears with its purpose to improve the quality of information, especially during COVID-19, where hoaxes spread massively. Moreover, a fact-checking organization needs to be more selective in choosing claims based on check-worthiness criteria, including Cek Fakta Tempo.co. The study described how Cek Fakta Tempo.co determine the check-worthiness of a claim during the COVID-19 pandemic. The study was conducted on case study methods to describe the dynamics and process during a claim selection. The data collection process occurred during February-July 2021, using an in-depth interview with Tempo.co fact-checkers, documentation, and literature study. The study found that Cek Fakta Tempo.co fact-checking methodology consists of three stages, pre-examination, fact-checking process, and post-examination. Moreover, the check-worthiness of a claim is determined at the pre-examination stage by conducting editorial meetings that rely on several considerations. The consideration includes five substantive criteria (viral claims, speaker impact, urgency, proximity, and intention) and also digital tools obtained from the external collaboration.